Development of Religious Moderation Measurements - Ghufron, M. Nur; Efferi, Adri (LP2M IAIN kUDUS, 2023)
This research with qualitative and quantitative approaches in order to develop measurements of religious moderation. There are stages that will be carried out, first determining the definition or concept of religious moderation, with a prototype methodology approach. Search, explain and describe individuals who have moderate nature in religion. Prototype methodology is used to obtain constructs of psychological variables, including cognitive, conative and psychomotor. Subsequent research compiles or develops measuring instruments for religious moderation. The first study was analyzed qualitatively, while the second study used quantitative analysis. Based on reliability tests with an alpha internal consistency approach, reliability was obtained of 0.90. Based on confirmatory analysis, it was found that chi-square 295.103 (DF = 164, p = 0.000), CMIN / DF = 1.799, GFI = 0.877, TLI = 0.887 and RMSEA = 0.062. Conclusion The criteria for acceptance of the model are met or have been as required. The proposed model design is the same as the empirical data or the model proposed fit. This means that religious moderation can be explained through tolerant behavior towards other people's religions and beliefs, having a national commitment, non-violence and being able to behave and behave accommodating with local culture.